Rast a prežívanie probiotických laktobacilov v lisovanom pohánkovom produkte - Liptáková, Denisa; Petruláková, Monika; Pelikánová, Jana; Valík, Ľubomír; Krištúfková, Kristína (Chemické listy, 2016)
The growth dynamics of Lactobacillus acidophilus 145 and Lb. rhamnosus GG in substrate prepared from buckwheat, water or milk, sucrose or flavoring compound (vanilla and chocolate) was investigated. In general, during the fermentation (numbers at the end have reached values from 1.8?108 to 3.4?109 cfu g1) or storage (Nfinal from 1.8?108 to 3.3?109 cfu g1), the growth of individual strain was satisfactory. According to the evaluation of overall taste, the substrate with vanilla flavor and water, fermented by Lb. rhamnosus GG for 24 h and stored for 5 days, obtained the highest number of points. Lactobacilli had slightly cytotoxic effect on the HeLa cells and Caco-2 cells, and the percentage of inhibition after 48 and 72 h of exposure ranged from 40 to 96 % for both selected strains.
Keywords: HeLa Cells; Probiotics; apoptóza; Diet, Gluten-Free; Apoptosis; Caco-2 buňky; lidé; HeLa buňky; Fagopyrum; fermentace; probiotika; Fermentation; bezlepková dieta; Celiac Disease; Lacticaseibacillus rhamnosus; Caco-2 Cells; Lactobacillus acidophilus; celiakie; Humans